Periodic Data Analysis and Forecasting As An Overview of Future Management Economics - Henderi, Henderi; Zuliana, Siti Ria; Pradana, Restu Adi (APTISI Transactions on Management (ATM), 2019)
In economics management is needed periodic data (time series) from production effort in predicting continuation of a situation is action which at one time must be done. For economic or political experts, it seems to be an obligation that must be carried out when they find a situation say just the economic crisis that befell a country with great, to provide predictive reviews about how the impact will be on the continuation of the existence of that country. So from that the aim of this research is to discuss about conceptual and conceptual aspects about periodic data, calculation of straight line trends through free method, half moving average, half average and least number of squares, non linear trend calculation which is trend parabola and exponential trends, calculations for changing trend equations into quarterly and monthly trends, calculations for changing trend equations into average trends, calculating seasonal variation values ​​through simple average methods, ratio to trend, ratio of moving averages and relative berangkai, and calculation of cyclic variation values ​​for annual and quarterly data. The method used during this study took place, namely using a literature study method which functions so that in research, researchers continue to add insight.